A General Method for N‐Methylation of Amines and Nitro Compounds with Dimethylsulfoxide. Issue 1 (10th December 2013) - Jiang, Xue; Wang, Chao; Wei, Yawen; Xue, Dong; Liu, Zhaotie; Xiao, Jianliang
Abstract DMSO methylates a broad range of amines in the presence of formic acid, providing a novel, green and practical method for amine methylation. The protocol also allows the one‐pot transformation of aromatic nitro compounds into dimethylated amines in the presence of a simple iron catalyst.